Organocatalyst bound -aminoalkyl radical intermediate for controlled aerobic oxidation of iminium ions - Motaleb, Abdul; Bera, Asish; Maity, Pradip (Organic & Biomolecular Chemistry, 2018)
A catalyst bound -aminoalkyl radical intermediate from iminium is developed to control its formation and reactivity with aerobic oxygen. The influence of the catalyst was demonstrated via the ease of radical intermediate formation and its subsequent reactivity, including the first catalyst-controlled enantioselective aerobic oxidation with a chiral phosphite catalyst.

Phosphite-Catalyzed C-H allylation of azaarenes via an enantioselective [2,3]-Aza-wittig rearrangement - Motaleb, Abdul; Rani, Soniya; Das, Tamal; Gonnade, Rajesh G.; Maity, Pradip (Angewandte Chemie-International Edition, 2019)
A phosphite-mediated [2,3]-aza-Wittig rearrangement has been developed for the regio- and enantioselective allylic alkylation of six-membered heteroaromatic compounds (azaarenes). The nucleophilic phosphite adducts of N-allyl salts undergo a stereoselective base-mediated aza-Wittig rearrangement and dissociation of the chiral phosphite for overall C-H functionalization of azaarenes. This method provides efficient access to tertiary and quaternary chiral centers in isoquinoline, quinoline, and pyridine systems, tolerating a broad variety of substituents on both the allyl part and azaarenes. Catalysis with chiral phosphites is also demonstrated with synthetically useful yields and enantioselectivities.